Association between kidney function, nutritional status and anthropometric measures in older people - Feldreich, Tobias; Carlsson, Axel; Freiberger, Ellen; Kob, Robert; Roller-Wirnsberger, Regina; Wirnsberger, Gerhard; Ärnlöv, Johan; Carlsson, Axel C.; Mattace-Raso, Francesco; Formiga, Francesc; Freiberger, Ellen; Sieber, Cornel; et al. (BMC Geriatrics, 2020)
Background: Different mechanisms connect the nutritional status with the occurrence and the course of chronic kidney disease (CKD). The end-stage renal disease is complicated by catabolic inflammatory reactions and cachexia which leads to malnutrition (undernutrition). On the other hand, obesity is an important risk factor for the development and acceleration of CKD. Methods: In the SCOPE study, community-dwelling persons aged 75 years and over, from 6 European countries and Israel were examined at the baseline phase. We assessed the relationship between anthropometric measures (Body Mass Index (BMI), circumferences of arm (AC), waist (WC), hip (HC), and calf (CC), waist-to-hip ratio-WHR, waist-to-height ratio-WHtR, risk of malnutrition (Mini Nutritional Assessment-MNA), serum albumin) and estimated glomerular filtration rate (eGFR) calculated by Berlin Initiative Study (BIS) equation. Results: We studied 2151 subjects (932 men and 1219 women) with a mean age of 79.5 ± 5.9 years. A total of 1333 (62%) participants had CKD (GRF < 60 ml/min/1.73 m2). Negative correlations between eGFR and weight, AC, WC, HC, CC, BMI, WHtR were observed. Positive correlation occurred between eGFR and MNA score (Spearman's rho = 0.11) and albumin concentration (rho = 0.09). Higher weight, AC, WC, HC, CC, BMI and WHtR increased the odds ratio of CKD; higher MNA (OR = 0.98, 95% CI 0.94-1.0) and higher serum albumin (OR = 0.73, 95% CI 0.53-1.0) were weakly associated with reduced odds. The risk of malnutrition was the highest with eGFR < 30 as compared to eGFR > 60 (OR = 2.95, 95%CI = 1.77-4.94 for MNA < 24; OR = 5.54, 95%CI = 1.66-18.5 for hypoalbuminemia < 3.5 g/dL). Conclusion: The population of community dwelling people aged 75+ with CKD shows general features of overweight and obesity with a small prevalence of malnutrition. For anthropometric measures, the strongest association with eGFR and the highest odds of CKD were identified using WC, HC, CC and WHtR. Albumin level and MNA, but not MNA Short Form, indicated an increased odds of malnutrition with a decrease in eGFR.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Aging; Chronic kidney disease; Malnutrition; MNA; Obesity; Overweight; Undernutrition